Peningkatan Pengetahuan Smartfarming Hydropro berbasis Internet of Things untuk Kelompok Wanita Tani Melati Mangkukusuman Kota Tegal - Afriliana, Ida; Basit, Abdul; Kurniawan, Safar Dwi; Maulana, Ahmad (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Melati Mangkukusuman Women Farmers Group is a community group of mothers who are active in household farming and urban farming activities by utilizing the Greenhouse land on Jl. Cereme, Tegal City. KWT Melati has problems in watering the seeds planted in the Greenhouse. This Community Service Program aims to improve the knowledge and skills of the Melati Women Farmers Group (KWT) of Tegal City regarding the application of Smartfarming Hydropro technology based on the Internet of Things (IoT). Method: Partners in this community service are members of KWT Melati MKK, with community service methods namely socialization, demonstrations, and simulations of automatic watering using the Hydropro tool, which can monitor and control watering and nutrition for tomato plants automatically or manually. Other materials are about planting hydroponic tomato cultivation from seed to transplanting. Results: The results of this community service are providing knowledge to the members of KWT Melati MKK about the internet of things, especially smartfarming. And also providing knowledge of tomato cultivation using hydroponics and how to harvest them. Conclusion: The target output of the activity is to understand how to water plants properly and be able to utilize IoT technology, by implementing hydropro to increase agricultural productivity in Green houses efficiently, cost-effectively, and support agricultural sustainability for the needs of housewives.